Developmental Differences in Infants' Attention to Social and Nonsocial Threats. (12th October 2016) - LoBue, Vanessa; Buss, Kristin A.; Taber‐Thomas, Bradley C.; Pérez‐Edgar, Koraly
Abstract : Research has demonstrated that humans detect threatening stimuli more rapidly than nonthreatening stimuli. Although the literature presumes that biases for threat should be normative, present early in development, evident across multiple forms of threat, and stable across individuals, developmental work in this area is limited. Here, we examine the developmental differences in infants' (4‐ to 24‐month‐olds) attention to social (angry faces) and nonsocial (snakes) threats using a new age‐appropriate dot‐probe task. In Experiment 1, infants' first fixations were more often to snakes than to frogs, and they were faster to fixate probes that appeared in place of snakes vs. frogs. There were no significant age differences, suggesting that a perceptual bias for snakes is present early in life and stable across infancy. In Experiment 2, infants fixated probes more quickly after viewing any trials that contained an angry face compared to trials that contained a happy face. Further, there were age‐related changes in infants' responses to face stimuli, with a general increase in looking time to faces before the probe and an increase in latency to fixate the probe after seeing angry faces. Together, this work suggests that different developmental mechanisms may be responsible for attentional biases for social vs. nonsocial threats.